Perceptions of parents, nurses, and physicians on neonatal intensive care practices - Latour, Jos; Hazelzet, J.; Duivenvoorden, H.; Van Goudoever, J. (Mosby, Inc., 2010)
Objective: To identify satisfaction with neonatal intensive care as viewed by parents and healthcare professionals and to explore similarities and differences between parents and healthcare professionals. Study design: A 3-round Delphi method to identify neonatal care issues (round 1) and to determine the importance of these issues (rounds 2 and 3) was conducted among nurses (n = 84) and physicians (n = 14), followed by an exploratory survey among parents (n = 259). Main outcome measures were 92 neonatal care-related items. Results: Sixty-eight nurses and 13 physicians completed all 3 rounds. The first round yielded 419 neonatal care related statements, which were clustered into 92 items. The survey was completed by 148 (57%) parents. Parents rated 25 of 92 care items significantly higher than did the professionals (effect size of Cohen's d, 0.31 to1.14, P = .02). Two items related to medication administration had the largest effect size. Professionals rated 7 items significantly higher than did parents (Cohen's d, -0.31 to -0.58, P = .04). One of these was assigning a physician and a nurse to the parents. Three were related to multicultural care. Conclusions: This study revealed disparities between parents and neonatal intensive care unit staff on a number of care issues reflecting incongruity in recognizing parents' desires. Copyright © 2010 Mosby Inc.